SISTEM PENILAIAN RAPOR PESERTA DIDIK BERBASIS WEB SECARA MULTIUSER - Damayanti Damayanti; Rifki Yudiantara; M Ghufroni An’ars (Universitas Teknokrat Indonesia, 2021)
SDN 1 Pardasuka is a public elementary school located in the Pringsewu area. The process of managing values at SDN 1 Pardasuka still has problems. The assessment process is carried out using written media on daily, mid-semester and semester assessment forms conducted by each teacher based on the subjects followed by students. At the end of each semester, data processing of all grades and student records is carried out to make an assessment report in the form of a student report card. The process of processing report cards by the homeroom teacher is still carried out repeatedly from teacher assessment notes to recap of student report cards, resulting in ineffective and efficient work in terms of time and effort. The solution to this problem is to implement a web-based report card value processing information system. The development of a web-based system provides convenience in managing student grades. The system development method used is extreme programming and produces an electronic student score management system with several features such as daily scores, knowledge scores, skill scores, social scores, spiritual scores and final exam scores.